Potential health risk for residents around a typical e-waste recycling zone via inhalation of size-fractionated particle-bound heavy metals - Huang, Chun-Li; Bao, Lian-Jun; Luo, Pei; Wang, Zhao-Yi; Li, Shao-Meng; Zeng, Eddy Y. (JOURNAL OF HAZARDOUS MATERIALS, 2016)
Health risk of residents dwelling around e-waste recycling zones has been a global concern, but has not been adequately examined. The present study was intended to evaluate the potential health risk of residents through inhalation exposure to size-fractionated particle-bound heavy metals in a typical e waste recycling zone, South China. Anthropogenic metals (Zn, Se, Pb, Sb, As, and Cd) were predominantly enriched in fine particles (D-P < 1.8 mu m), whereas the crustal elements,(Ti, Fe, and Co) tended to accumulate in coarse particles (D-p > 1.8 mu m). Although the daily inhalation intakes of the target metals were significantly lower than those through food consumption and ingestion of house dust, the hazard quotients of total metals for adults (95% CI: 1.0-5.5) and children (95% CI: 3.0-17) were greater than 1. Moreover, the incremental lifetime cancer risks of five carcinogenic metals (Cr, Co, Ni, As, and Cd) for adults and children were 1.3 x 10(-3) (95% CI: 4.1 x 10(-4)-3.0 x 10(-3)) and 3.9 x 10(-3) (95% CI: 1.3 x 10(-3)-8.6 x 10(-3)), respectively, substantially higher than the acceptable cancer risk range of 10(-6)-10(-4). All these findings suggested that health risks were high for local residents dwelling around the e-waste recycling zone through inhalation exposure to particle-bound heavy metals, for both adults and children. (C) 2016 Elsevier B.V. All rights reserved.